2022
DOI: 10.1038/s41598-022-05462-x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and nutritional value of silkworm (Bombyx mori) pupae-fortified chicken bread spread

Abstract: This study aimed to apply silkworm pupae (SP) to food product development. The characteristics and sensory acceptance of chicken bread spread fortified with SP at different levels (0%; SP0, 25%; SP25, 50%; SP50, and 75%; SP75) were evaluated. The fat content of the bread spread was significantly increased, whereas the protein content was decreased with increasing levels of SP (p ≤ 0.05). The increased level of SP resulted in the final products being dark in color, as indicated by the significant decrease in L*… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Due to their properties, silkworm pupae have been widely used in food, pharmaceutical, textile, and other industries [ 22 , 100 , 101 ]. Silkworm pupae are being used to develop new food products, and pupae protein and oil have been reported as alternative sources of protein and fat for bread making [ 13 ].In the future, the consumption of silkworm pupae will not just be limited to direct consumption, but a variety of new food products will be developed that contain silkworm pupae. As pupae are rich in protein, they can be used as a high-protein food for human consumption and as an ideal material for nutritional feed for animals [ 4 , 22 ].In addition, the high-protein properties of silkworm pupae can be used as bioreactors to express exogenous proteins [ 71 ].…”
Section: Application Prospects Of Silkworm Pupaementioning
confidence: 99%
See 2 more Smart Citations
“…Due to their properties, silkworm pupae have been widely used in food, pharmaceutical, textile, and other industries [ 22 , 100 , 101 ]. Silkworm pupae are being used to develop new food products, and pupae protein and oil have been reported as alternative sources of protein and fat for bread making [ 13 ].In the future, the consumption of silkworm pupae will not just be limited to direct consumption, but a variety of new food products will be developed that contain silkworm pupae. As pupae are rich in protein, they can be used as a high-protein food for human consumption and as an ideal material for nutritional feed for animals [ 4 , 22 ].In addition, the high-protein properties of silkworm pupae can be used as bioreactors to express exogenous proteins [ 71 ].…”
Section: Application Prospects Of Silkworm Pupaementioning
confidence: 99%
“…Gradually, the pupae have been further processed to extract nutrients and active ingredients and are used in food modification and pharmaceutical development [ 13 ]. Some researchers have used silkworm pupa powder as a protein enhancer in functional foods, and the addition of silkworm pupa powder enhances the flavour and taste of functional foods [ 13 , 14 , 15 ]. Examples are bread, yogurt, and food additives [ 7 , 13 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant differences were found in carbohydrate content between the control sample and the fish paste samples containing SWP powder. According to previous studies reported, increasing levels of SWP powder decreased the protein content of chicken bread spread and meat batter, while fat content increased (Park et al, 2017 andKarnjanapratum et al, 2022). It can be concluded that the energy value of processed fish paste formulas with SWP was increased (Table 3).…”
Section: The Chemical Composition Of Fish Pastementioning
confidence: 63%
“…The same trend was reported by Kim et al (2016), who found that the addition of SWP flour slightly increased the pH of emulsion sausage. On the other hand, Karnjanapratum et al (2022) reported that SWP levels had no significant effect on the pH of the final product of chicken bread spread because there were no significant differences in pH between chicken breast and SWP. The TBA values of the different fish paste formulas ranged from 0.061 to 0.067 mg malondialdehyde kg sample (Table 4).…”
Section: Physicochemical Propertiesmentioning
confidence: 98%